(untitled) (Economics and region, 2025)
The article examines the organizational and economic mechanism necessary for the management of oil and gas fields, focusing on their role in optimizing the production, processing and distribution of hydrocarbon resources. The mechanism involves a complex interaction of management strategies, economic policy, technological innovation and regulatory frameworks aimed at maximizing productivity while minimizing environmental impact and operating costs. By analyzing the fundamental principles and key components of this framework, the study highlights the factors that contribute to operational efficiency, economic viability, and sustainable practices in the industry. The article also examines the challenges associated with fluctuations in market dynamics, environmental problems and technological failures, as well as offers insights on how to optimize the organizational and economic mechanism to increase the competitiveness and sustainability of the oil and gas sector in Ukraine. Ultimately, the study aims to facilitate discussions on improving the attractiveness of the investment of the industry, encouraging innovation, and ensuring the responsible exploitation of hydrocarbon resources for future generations.